Grasses of the Upper Gangetic Plain - Pooideae - Raizada, M. B.; Jain, S. K . (Indian Forester, 1966)
The following paper is a precursor of the authors’ third and final part of the work ’Grasses of the Upper Gangetic Plain’. A list of the species of the subfamily Pooideae proposed to be included in that work is given; it includes 133 taxa. The authors will be grateful if any additional species of the Pooideae collected or noted by any worker from the area of the Upper Gangetic Plain are brought to their notice; this help will be duly acknowledged.